Түркий көркем дүньясы (FAN va JAMIYAT, 2026)
The article discusses the evolution of the development of Turkic peoples’ literature, including Uzbek, Karakalpak, Kazakh, Kyrgyz, and Turkmen literature. It examines the artistic sources of these literatures, issues of literary influence, creative interconnections, as well as the unity of artistic form and content.